Beyond disintermediation: A multiple case study of emerging intermediary roles in blockchain applications - Simon Feulner; Tobias Guggenberger; Nils Urbach (Electronic Markets, 2025)
Since the introduction of blockchain technology, both academic and practical discourse has explored its impact on intermediation. Early research emphasized the notion of disintermediation, removing traditional intermediaries through decentralized trust and automated coordination. Yet, more recent studies highlight that blockchain systems often give rise to new forms of intermediation. These roles may not resemble legacy intermediaries but nonetheless fulfil essential functions such as compliance, governance, and technical integration. Based on a multiple case study, we investigate how and why such re-intermediation occurs in blockchain ecosystems. Our analysis identifies three recurring drivers, system integrity and resilience, boundary and interface management, and governance efficiency, that structurally necessitate new coordination layers. This study thereby contributes to electronic markets and blockchain literature by offering a refined conceptualization of intermediation dynamics in distributed systems.
Keywords: L1; M0; O30; 620; Disintermediation; Re-intermediation; Blockchain; Multiple case study